Defisit Air Pada Berbagai Fase Pertumbuhan dan Pengaruhnya Terhadap Karakter Kuantitatif Beberapa Genotipe Kacang Tanah - A Farid Hemon; Sumarjan Sumarjan; Baiq Erna Listiana; Suprayanti Martia Dewi (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
This study aims to determine the effect of water deficit at various phases of plant growth on the quantitative characters of several peanut genotypes. This study used a completely randomized design-split plot design.  The water deficit consisted of 6 treatments: d0 = no water deficit, d1 = water deficit from germination to harvest, d2 = water deficit from germination to age 25 days after planting (dap) (vegetative phase), d3 = water deficit from age 26  to 50 dap (flowering phase to pod formation), d4 = water deficit from age 51 dap to 75 dap (seed filling phase), and d5 = water deficit from age 75 dap to 100 dap (seed ripening phase until harvest). The peanut genotype used consisted of 10 genotypes. The results showed that water deficit in various phases of plant growth resulted in different quantitative characters in several peanut genotypes. Genotype G3T4 produced heaviest dry pod weight of 12.7 g plant-1 in water deficit from germination to harvest. Genotype G200-I produced heaviest dry pod weight of 11.5 g per plant-1 in water deficit in the vegetative phase. Genotype G3T4 produced heaviest dry pod weight of 13.3 g per plant in water deficit the generative phase. Genotype G300-II produced heaviest the dry pod weight of 11.7 g per plant-1 in the water deficit of the seed filling phase. Genotypes G2D2, G2T3 and G200-I produced the heaviest dry pod weight of 11.0 g per plant-1 in the water deficit of the seed ripening phase.